A comparative study of empirical and analytical fragility functions for the assessment of tsunami building damage in Tumaco, Colombia. Issue 3 (2nd July 2020) - Paez-Ramirez, Juan; Lizarazo-Marriaga, Juan; Medina, Sergio; Estrada, Martin; Mas, Erick; Koshimura, Shunichi
ABSTRACT: A fragility function shows the building damage likelihood based on a demand parameter such as the tsunami flow depth. While empirical fragility functions have been developed by using postdisaster damage survey data, regions with no recent tsunami damage cannot develop these estimations. Alternatively, analytical fragility functions could be developed to fill this gap. Along the Colombian Pacific coast, several tsunami events have occurred; however, the aftermath resulting from the structure physical damage was not recorded. Fortunately, other regions of the have collected tsunami damage information, which has been analyzed and represented in terms of empirical fragility functions. This paper provides a comparative study of empirical and analytical tsunami fragility functions. It is focused on the analytical fragility functions developed for typical structures in Tumaco, Colombia and on empirical fragility curves taken from damage survey data of recent tsunami events. The differences in the assessments of the damage produced by the two methods in the case of a two-story reinforced concrete building in Tumaco is discussed herein. As a result of the comparison, it was shown that the structures in Tumaco have higher collapse probabilities at lower flow depths than structures in other places along the Pacific and Indian Oceans.